Hospitality, Revolution and the Emigrant Experience: Guests and Hosts in French Revolutionary Novels of Emigration Written by Women Authors - Bokobza Kahan, Michèle (Dalhousie French Studies, 2022)
This article examines the presence of hospitality as a significant theme in four French Revolutionary novels of emigration written by three major female authors of that time, Isabelle de Charrière, Claire de Duras and Stéphanie de Genlis. It aims to highlight the multiple facets of the concept of hospitality in these novels and to demonstrate that beyond its traditional meaning, hospitality operates too in political, social and ethical realms: 1) it becomes the pivot of an introspective reflection: a critical look at the conventions and social practices of the French nobility, 2) it reflects a political thought: tensions between condemnation and loyalty to the Old Regime system, and between adherence to and suspicion of republican ideals, 3) last but not least, it opens a path to a feminist approach through situations that stage relationships of help and care by émigré women for émigré women. The reading angle that I propose in the article confirms the originality of these novels that link emigration and hospitality by evoking the potentiality of new situations, no matter how painful they may be: flexibility, emancipation, adaptation, openness, sharing and care are key themes that recur in the narratives to underline the transformative power of mutual support, responsibility and trust between women.